2015
DOI: 10.1111/ejn.12904
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence of alterations to the nucleus accumbens and dorsolateral striatum during chronic cocaine self‐administration

Abstract: As drug use becomes chronic, aberrant striatal processing contributes to the development of perseverative drug-taking behaviors. Two particular portions of the striatum, the nucleus accumbens (NAc) and the dorsolateral striatum (DLS), are known to undergo neurobiological changes from acute to chronic drug use. However, little is known about the exact progression of changes in functional striatal processing as drug intake persists. We sampled single-unit activity in the NAc and DLS throughout 24 daily sessions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 77 publications
5
27
0
Order By: Relevance
“…The present study used D1‐Cre and D2‐Cre mice, which are well categorized and highly representative of endogenous D1 and D2 neurons in the direct and indirect pathways (Gerfen et al ., ). We were able to unambiguously identify those neurons by their response to a brief 5 ms light pulse, and we are confident in our ability to record just a single neuron on any given wire across multiple recording sessions (Coffey et al ., ). We chose a conservative identification procedure with a short light pulse to ensure that the neurons classified as D1 and D2 MSNs were in fact directly sensitive to the light stimulation and not to secondary stimulation (e.g., through multisynaptic activation).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study used D1‐Cre and D2‐Cre mice, which are well categorized and highly representative of endogenous D1 and D2 neurons in the direct and indirect pathways (Gerfen et al ., ). We were able to unambiguously identify those neurons by their response to a brief 5 ms light pulse, and we are confident in our ability to record just a single neuron on any given wire across multiple recording sessions (Coffey et al ., ). We chose a conservative identification procedure with a short light pulse to ensure that the neurons classified as D1 and D2 MSNs were in fact directly sensitive to the light stimulation and not to secondary stimulation (e.g., through multisynaptic activation).…”
Section: Discussionmentioning
confidence: 99%
“…This is true for both the body examination and the optogenetic identification. Statistical analysis of this technique has shown that the waveforms we record on a single wire are significantly more likely to belong to a single neuron, than to two or more neurons (Coffey et al, 2015).…”
Section: Electrophysiological Recordingmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the extent to which these mesoaccumbens DA-glutamate fibers participate in the neurobiology of drugs of abuse remains to be determined, we speculate that these axons may participate in the regulation of neuronal activity in cocaine self-administration. Specifically, electrophysiological recordings have shown that nAcc neurons exhibit rapid phasic firing patterns to related cues and actions to obtain the drug (Peoples et al, 1998; Ghitza et al, 2003, 2004, 2006; Fabbricatore et al, 2009, 2010; Coffey and Barker et al, 2015). The nAcc neurons also exhibit slow-phasic and tonic changes in firing rate that correlate with the pharmacological effects of cocaine, and do not correlate with the rapid phasic firing patterns (Fabbricatore et al, 2010).…”
Section: Functional Diversity By Vta Neuronsmentioning
confidence: 99%
“…In an initial study by Belin and Everitt (), using intrastriatal disconnection procedures, it was shown that interactions between ventral and dorsal areas in the striatum, mediated by dopamine, are crucial in the development of habitual cocaine‐seeking. These findings have been confirmed and extended in the context of addiction studies in more recent years, not only behaviorally but also using neurophysiological and neurochemical approaches (Adermark et al, ; Burton, Nakamura, & Roesch, ; Coffey et al, ; Keramati & Gutkin, ; Saddoris, Wang, Sugam, & Carelli, ; Willuhn, Burgeno, Everitt, & Phillips, ; Willuhn, Burgeno, Groblewski, & Phillips, ). Recent studies also show “spiraling” between the Acb‐s and Acb‐c in the context of behavioral actions and the transition from impulse control disorders into compulsive disorders (e.g., Besson et al, ; Diergaarde et al, ).…”
Section: Discussionmentioning
confidence: 62%